2020
DOI: 10.1093/rheumatology/keaa315
|View full text |Cite
|
Sign up to set email alerts
|

Global, regional, and national burden of other musculoskeletal disorders 1990–2017: results from the Global Burden of Disease Study 2017

Abstract: Objectives To describe the level and trends of point prevalence, deaths and disability-adjusted life years (DALYs) for other musculoskeletal (MSK) disorders, i.e. those not covered by specific estimates generated for RA, OA, low back pain, neck pain and gout, from 1990 to 2017 by age, sex and sociodemographic index. Methods Publicly available modelled estimates from the Global Burden of Disease (GBD) 2017 study were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 12 publications
1
46
0
2
Order By: Relevance
“…To compare the trends over two decades, we analyzed the related data in 1997, 2007, and 2017. The GBD study design and methods have been described in previous literature (21)(22)(23).…”
Section: Data Sourcesmentioning
confidence: 99%
“…To compare the trends over two decades, we analyzed the related data in 1997, 2007, and 2017. The GBD study design and methods have been described in previous literature (21)(22)(23).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Although the global burden of specific musculoskeletal disorders has been reported in previous studies (7–15), and included in multiple Lancet articles (16,17), no study to date has provided an overview of the burden of all musculoskeletal disorders combined in a single article. One 2003 review reported the burden of major musculoskeletal disorders (18), although new data are available that supersede the results of that study.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) and cardiovascular diseases (CVD) are the most prevalent conditions in developed countries, contributing to the global health burden worldwide, due to pain, disability, loss of work and cost of treatment [ 1 , 2 ]. The prevalence of OA increases due to the aging population, as does the prevalence of many other disabling conditions co-occurring or co-existing with OA, named “comorbidities”, which may worsen patient global well-being.…”
Section: Introductionmentioning
confidence: 99%